The effects of field inoculation of arbuscular mycorrhizal fungi through rye donor plants on grapevine performance and soil properties - Nogales, Amaia (2021)
Grapevines are highly dependent on arbuscular mycorrhizal fungi (AMF) for normal growth and development. However, vineyard soils may have low AMF abundance and diversity due to conventional soil management practices that are detrimental for these fungi. In this context, the establishment of AMF-inoculated cover crops can be a highly convenient strategy to reestablish soil mycorrhizal potential, as it combines the advantages of a vigorous inoculum source coming from mycorrhizal donor plants with the overall benefits of green covers for grape quality, microbial diversity and soil health. In this work, the potential benefits of Funneliformis mosseae-inoculated under-vine cover crops on grapevine growth, physiology and production were compared to those derived from 1) the establishment of non-inoculated under-vine cover crops, and 2) conventional herbicide-based weed control in the under-vine space. In addition, grapevine root AMF community composition was analyzed to assess if the introduction of a non-native AMF species induced changes on resident mycorrhizal community assemblies and to unveil potential variations in AMF diversity associated to herbicide replacement by green covers. Results indicated that under-vine cover crops, inoculated or not, led to a general vigor decrease in grapevines, probably due to competition between the two species. However, after a heat wave that occurred at harvest time in the second year of the experiment, grapevines growing in plots with inoculated cover crops had the highest photochemical reflectance indices and net photosynthesis rates, and partially compensated production losses due to berry sunburn. Root mycorrhizal community analysis by the end of the experiment revealed that the inoculated F. mosseae isolate colonized grapevine roots from inoculated plots, while it was absent in the other ones. Moreover, inoculation of this AMF did not lead to a replacement of native root AMF communities, but allowed further colonization by other resident Glomeraceae and non-Glomeraceae AMF taxa. Overall, the work herein demonstrates that the introduction of F. mosseae through donor plants is a suitable field inoculation method for grapevines and can help them to better withstand heat waves